2016
DOI: 10.1002/etc.3576
|View full text |Cite
|
Sign up to set email alerts
|

Population modeling for pesticide risk assessment of threatened species—A case study of a terrestrial plant, Boltonia decurrens

Abstract: Although population models are recognized as necessary tools in the ecological risk assessment of pesticides, particularly for species listed under the Endangered Species Act, their application in this context is currently limited to very few cases. The authors developed a detailed, individual-based population model for a threatened plant species, the decurrent false aster (Boltonia decurrens), for application in pesticide risk assessment. Floods and competition with other plant species are known factors that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 43 publications
(76 reference statements)
0
24
0
Order By: Relevance
“…This suggests that relying on individual-level responses as proxies of impacts of multiple stressors could seriously underestimate the risks for populations and ecosystems. Interestingly, many modelling studies evaluating impacts of individual stressors found that population responses are the same or lower than those at the level of individuals, usually due to density-dependent buffering mechanisms (Forbes et al 2001;Galic et al 2017;Schmolke et al 2017), but see Gergs et al (2013).…”
Section: Responses To Stressors At Different Levels Of Biological Orgmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that relying on individual-level responses as proxies of impacts of multiple stressors could seriously underestimate the risks for populations and ecosystems. Interestingly, many modelling studies evaluating impacts of individual stressors found that population responses are the same or lower than those at the level of individuals, usually due to density-dependent buffering mechanisms (Forbes et al 2001;Galic et al 2017;Schmolke et al 2017), but see Gergs et al (2013).…”
Section: Responses To Stressors At Different Levels Of Biological Orgmentioning
confidence: 99%
“…Assessing impacts on populations based on individual-level responses can result in errors because of many compensatory or depensatory processes and feedbacks across levels of organisation. Previous studies have shown that effects of isolated stressors on populations are not necessarily proportional to those on individuals, and can be of lesser (Galic et al 2017;Schmolke et al 2017) or greater magnitude (Gergs et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Relative effects of stressors on populations may differ depending on whether the population is stable, declining, or increasing (Calow et al ; Salice ; Schmolke et al ). For the main simulation results given in the present study, we assumed stable populations in the untreated controls.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, population models can be used to represent available information about the life history and ecology of a species and combined with organism‐level exposure–effects relationships from surrogate species to assess potential population‐level effects of pesticide exposures over extended time periods (Forbes et al ; Schmolke et al ). Species‐specific population models developed for pesticide risk assessments can be used as platforms to assess potential risks from various pesticides or other stressors, rather than being specific to the risk assessment of a single compound (Schmolke et al ). However, population models specifically developed for and applied to pesticide risk assessments are still relatively rare (Forbes et al ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, one can simulate temperature and/or food fluctuations and calculate their effects on individual metabolism at each time step (Accolla et al 2019). Other environmental drivers can be hydrological variability and water turbidity (Railsback et al 2009; Focks, ter Horst et al 2014), flooding (Schmolke, Brain et al 2017), or flowering periods that affect pollinator foraging (Becher et al 2014). Alternatively, states of agents may vary according to a pattern defined by the day of the year or season.…”
Section: Key Features To Consider In Model Development and Evaluationmentioning
confidence: 99%